Formulation and Characterisation of Nanosuspension of plant extract Cocculus Pendulus - Sampath Kumar Ramala (Journal of Global Pharma Technology, 2019)
ABSTRACT:Nanotechnology is a promising technique to increase the bioavailability of herbal medicines. The present study was  formulated to evaluate nanoparticles using an ethanolic extract of Cocculus pendulus. The sonoprecipitation technique was employed for the preparation of nanosuspensions with poloxamer-407 and PVA with many trails and finally the optimized nanosuspension demonstrated a mean particle size, polydispersity index, and zeta potential of 536 nm, 0.256, and − 17.6 mV, respectively. The results of the characterization studies illustrated that the nanosuspension was in the nanometer size range and spherical in shape had good surface morphology. The present outcomes clearly demonstrated that to obtain an effective therapeutic potential, nanoformulation of medicinal plants is a better alternative than conventional dosage forms. Key words:Nanosuspension, sonoprecipitation, mean particle size, polydispersity index, and zeta potential